The Effect of Small Movement Games On Improving Some Referential Thinking Skills and Academic Achievement In Fifth Grade Science Class - AbdMajeed, Rana (Journal of Physical Education, 2016)
The importance of the study lies in thinking and the different methods used toimprove it. The researcher used a teaching program including small games in physicaleducation class to explain fifth grade primary school science. The researcher aimed tidentifying the effects of these games on referential thinking and academic achievement. Theproblem of the research lies in difficulties faced by students in science class. The aim of theresearch was to identify the effect of small movement games in improving referentialthinking and academic achievement in science class / primary school. The researcherhypothesized statistical differences between experimental and controlling groups inimproving referential thinking and academic achievement in favor of the experimental group.The researcher used the experimental method. The results showed positive effect of smallgames in physical education class to improve referential thinking and academic achievementin science class. The researcher recommended the necessity of making a program for scienceclass as well as other classes that concentrates on all thinking skills in general and referentialthinking in particular.